Pendampingan Kegiatan Masa Kesetiaan Anggota (Makesta) IPNU-IPPNU Komisariat Madrasah Aliyah Takhassus Al-Qur’an Wonosobo - Abdurrohman Al Asy’ari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
) activities for Madrasah Aliyah Takhassus Al-Qur'an students in Wonosobo Regency. The mentoring stages go through four steps: coordination, implementation, FGD, and activity evaluation. Qualitative research setting by collecting data through observation, interviews, Focus Group Discussions (FGD), and filling out questionnaires. The results of this activity show that assistance in the Member Loyalty Period activity is very effective in strengthening awareness of good attitudes in life. The specific positive impact of this activity was an increase in understanding of the culture of healthy living and the importance of organizing. A follow-up mentoring program is needed so that activity alumni can further develop their mindset and organizational spirit.